In Vitro Anti-Wrinkle and Tyrosinase Inhibitory Activities of Grapefruit Peel and Strawberry Extracts - Endang Lukitaningsih; Syamsu Nur; Fadilah Qonithah; Andi Zulbayu; Rina Kuswahyuning; Rumiyati Rumiyati (Faculty of Pharmacy, Universitas Gadjah Mada, 2020)
The research aims to analyse the antioxidant, anti-tyrosinase and anti-wrinkle activities from grapefruit (Citrus Maxima L) and strawberry extracts. Samples were extracted by maceration using 96% ethanol and ethyl acetate, subsequently. The Ferric Reducing Antioxidant Power (FRAP) and β-carotene bleaching (BCB) were used to measure the antioxidant activity. The effect of anti-wrinkle was determined by testing the inhibition of elastase and collagenase enzyme, while anti-tyrosinase activity was analysed using mushroom tyrosinase enzyme. The results showed that strawberry extracts in ethanolic (SE) and ethyl acetate (SEA) have antioxidant activity in FRAP (EC50 = 404.39 ± 3.27 µg / mL and 1978.65 ± 37.25 µg/mL) and BCB (IC50 = 292.30 ± 4.69 µg/mL and 671.11 ± 6.74 µg/mL). Whereas the grapefruit peel extracts both in ethanolic (GPE) and ethyl acetate (GPEA) have antioxidant activity in FRAP (EC50 219.47 ± 71.96 µg / ml and 309.44 ± 95.76 µg/ml) and BCB (EC50 245.19 ± 162.47 µg/ml and 567.54 ± 95.31 µg/ml). As positive standards for FRAP antioxidant analysis were quercetin and vitamin C which has IC50 respectively 18.97 ± 4.50 µg/mL and 24.47 ± 1.44 µg/mL. While in BCB analysis, Butylated Hydroxy Toluene (BHT) used as positive standard (IC50 38.68 ± 5.70 µg/mL). The samples of SE, SEA, GPE and GPEA showed tyrosinase inhibitory activity which the IC50 values were respectively 492.68 ± 1.43; 2658 ± 48.08; 3312.5 ± 222.74; 2985.17 ± 122.80 µg/ml. Kojic acid (IC50 111.52 ± 0.42 µg/ml) is used as positive standard in this study. In addition, SE, SEA, GPE and GPEA were able to inhibit elastase and collagenase enzymes, although their activities were still lower than the positive standard used in this study. Elastastinal in concentration 50 µg/mL giving elastase inhibition about 71.71 ± 0.81 µg/mL, while vitamin C in the same concentration showed collagenase inhibition about 66.79 ± 1.23 µg/mL. It can be concluded that the extract of strawberry and grapefruit peel has antioxidant, anti-tyrosinase and anti-wrinkle activity through inhibition of elastase and collagenase enzymes; thus, they can be used as antiaging cosmetic ingredients.